2020
DOI: 10.1002/htj.21910
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the heat transfer characteristics of propylene glycol–water mixture in the shell side of a spiral‐wound heat exchanger

Abstract: The heat transfer characteristics of propylene glycol-water (PG-W) mixture (10%, 20%, and 30% propylene glycol) on the shell side of a spiral-wound heat exchanger (SWHE) were investigated experimentally. Among the SWHE selected, there are 18 twined tubes with a diameter of 8 mm. PG-W mixture is on the shell side and water is on the tube side. The results show that the heat transfer coefficient of PG-W mixture flowing downwards is higher than upwards under countercurrent conditions. The heat transfer coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…In general, the vortex distribution area in the quasisteady-state calculation was extensive, and the quasi-steady-state assumption could not be used to predict transient behavior. The other behavior is also found in other flow (Gu et al (2020), Abed et al (2020), Xue et al (2022), Dai et al (2021)).…”
Section: Introductionsupporting
confidence: 75%
“…In general, the vortex distribution area in the quasisteady-state calculation was extensive, and the quasi-steady-state assumption could not be used to predict transient behavior. The other behavior is also found in other flow (Gu et al (2020), Abed et al (2020), Xue et al (2022), Dai et al (2021)).…”
Section: Introductionsupporting
confidence: 75%
“…It is found that the fluid flow and the duration of the circuit during pump stop is affected by the inertia of the pump rotor and the fluid inertia. Moreover, some transient behavior is also found in other classical flow (Abed et al (2020), Gu et al (2020)).…”
Section: Introductionsupporting
confidence: 56%
“…In addition, the secondary flow induced by the centrifugal force in helically coiled tubes leads to better heat transfer rates as seen in heat exchangers for various applications (Naphon and Wongwises, 2006;Gu et al, 2020). Many studies have investigated the heat transfer in helically coiled tubes to study the effects of the geometric and flow parameters on the heat transfer (Ghorbani et al, 2010;Piazza and Ciofalo, 2010;Chingulpitak and Wongwises, 2010;Ferng et al, 2012).…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%